Government Instruments - Misdin Arifin HM; Setiawan Wijaya (Program Pascasarjana UIN Sumatera Utara Medan, 2020)
Government instruments are fundamental elements in the implementation of government functions based on the principle of the rule of law (rechtsstaat). In the practice of State Administrative Law, every action, decision, or policy taken by public authorities must be based on valid legal instruments. This is crucial to prevent abuse of authority (detournement de pouvoir) and arbitrary actions that have the potential to violate the constitutional rights of citizens. This paper is motivated by the need for a deep understanding of the transformation of government legal instruments in the increasingly complex modern era, especially in maintaining a balance between bureaucratic effectiveness and legal protection for the community. This research uses a normative juridical method by integrating a statute approach and a conceptual approach. The results of the study indicate that government instruments which include laws and regulations (regeling), state administrative decisions (beschikking), policy regulations (beleidsregel), discretion, and factual actions (feitelijke handelingen) have a strategic role in the dynamics of national law. These instruments function as legal means to guarantee legal certainty and provide protection mechanisms for citizens through means of objections and lawsuits. The proper arrangement of instruments is crucial for the realization of accountable, transparent governance, and in accordance with the General Principles of Good Governance (AAUPB). This study concludes that strengthening legal control over government instruments is an absolute prerequisite for preventing maladministration and strengthening the pillars of democracy.